(untitled) (Scientific journal of the Fergana State University, 2026)
This article discusses theoretical approaches in linguistics and ethics by analyzing axiological lexicons that express ethical-civic values. The article clarifies the semantic types of lexical units, namely the concepts of virtue and vice, as well as civic values (freedom, justice, equality, democracy). The study examines the historical evolution of words, adjectives, collocations, and expressions, their origins, and modern usage in various contexts. Based on a review of the theoretical literature, the ideas of A.F. Lago, T.P. Krzeszovskiy, P. Pauvels, and S. Vandenberg are analyzed, enriching the system of axiological lexicons. The article, grounded in scientific research, highlights the linguistic expression of moral-social values and contributes to the enhancement of language practice in cultural and political spheres. Both theoretical approaches and empirical analysis methods are presented, as illustrated by examples from oral and written communication. The research findings are expected to stimulate the formation of new perspectives in linguistics, ethics, and cultural studies, as well as lead to a deeper understanding of the macrostructure of values. In this way, the article generates considerable interest within the academic community and contributes to improving the overall effectiveness of scientific experience and theoretical approaches.